ONLINE EMPLOYEE DAILY REPORT DESIGN IN THE MAINTENANCE DIVISION OF PT.KRAKATAU BANDAR SAMUDERA - Reni Haerani (Journal of International Conference Proceedings (JICP), 2019)
This study aims to design and build applications to manage reports of daily activities of web-based employees with PHP and MySQL, as a substitute for conventional reports using paper reports in the Maintenance Division of PT. Krakatau Bandar Samudera. This type of research is Research and Development. Software development method using Waterfall Model. Software testing is done through black-box testing. In this research observation and interview to eight employees who work as a leader and supervisor in the Maintenance Departement. The results of this study is a web-based reporting applications using PHP and MySQL. So with this online reporting application makes the process of information transfer between leaders and Supervisors more quickly and effectively. And existing data can be managed for more complex purposes.